Re-envisioning the artificial intelligence-entrepreneurship nexus: a pioneering synthesis and future pathways - Fidel Isheanesu Mugunzva; Ntise Hendrick Manchidi (Insights into Regional Development)
The rapid advancement of artificial intelligence (AI) is profoundly transforming the entrepreneurial landscape while presenting a myriad of opportunities and challenges. However, scholarly inquiries into this pivotal intersection remain fragmented and lack a comprehensive and interdisciplinary understanding. This study provides a systematic review that consolidates insights from across AI, innovation and entrepreneurship literature to provide an integrated examination of the AI-entrepreneurship nexus. Through rigorous analysis of 92 studies, key themes are elucidated, including AI's impact on opportunity recognition, business model reinvention and socio-economic dynamics. An original Socio-Technical Systems framework is proposed, capturing the interplay between AI adoption decisions, AI-augmented opportunity exploration, innovative AI configurations and broader socio-economic consequences. While acknowledging AI's transformative potential, the review sounds a clarion call for responsible scholarship that centres on equity and social justice. It advocates a reflexive, inclusive approach, allowing marginalised voices and alternative perspectives to emerge. Theoretical contributions are made by extending established frameworks from technology adoption, business models and socio-technical systems to the AI-entrepreneurship context. Furthermore, actionable implications are provided for policymakers to develop governance models balancing innovation and ethical oversight. Therefore, entrepreneurs and support organisations are guided in facilitating responsible AI integration across diverse ecosystems. This unprecedented cross-disciplinary synthesis illuminates crucial gaps, charting an agenda for future research on transparency, accountability and mitigating AI's unintended impacts. As AI continues reshaping entrepreneurial frontiers, this review catalyses a trajectory of ethically- conscious scholarship poised to shape inclusive technological progress aligned with human values and societal wellbeing.